Reframing the Impact on Documentary From Social Media and Streaming Through Media Theories Informed by Platformization. - MAHER, SEAN (International Journal of Communication (19328036), 2024)
The analysis of documentary filmmaking is approached through emerging critical media theories responding to the intersections between Web-based platforms and factual programming. Despite series-based documentary becoming a mainstay on streaming services and inchoate forms of factual content proliferating across social media, scarce attention is paid to the context and role of Web-based platforms and their impact on documentary as a social movement media. Reframing critical media theory to account for the upheavals affecting documentary means taking fuller account of “platformization” and reexamining film history epistemologies of documentary premised on professional producers and spectatorship. As the era of globally networked communication continues to reconfigure iterations of certain social, political, and economic apparatuses, the analysis examines emerging approaches and speculative media theories to documentary as a key legacy media object. As the forerunner to a form of media that targeted social change, documentary warrants efforts to expand epistemological perspectives on its development and continued negotiation of social media in the age of Web-based communications.